Could Artificial Intelligence Replace Human Jobs in Framing of Online Media News CNN Indonesia and Detik.com? - Mahaputra, Muhamad Bagas; Febriana, Poppy (Procedia of Social Sciences and Humanities, 2024)
The purpose of this research is to find out how online media CNN Indonesia and Detik.com frame the news of Artificial Intelligence (AI) replacing human jobs. This research uses Robert N. Entman's framing analysis model, which can later find out how the framing is built through protrusion or emphasis in it so that it can find out the potential public trust in AI from the issue. The two online media have the same framing, both emphasising positive and negative things, besides AI can replace human jobs, AI is also beneficial for humans. Detik.com is considered more active in publicising this issue. The emphasis on the positive from both media on the counter issue has the potential to build public trust in AI, which also has an impact on the further development of AI as a useful technology.